THE INFLUENCE OF KNOWLEDGE OF ENTREPRENEURSHIP, SELF-EFFICACY TOWARDS INTERESTS ENTREPRENEURSHIP THROUGH MOTIVATION ENTREPRENEURSHIP TO SANTRI AT PONDOK PESANTREN BAHRUL MAGHFIROH MALANG - Yulian Muzakki; Agung Winarno; Ely Siswanto (International Journal of Economy, Education and Entrepreneurship, 2022)
The presence and role of santri in entrepreneurship can positively influence economic conditions and progress. For this reason, students from the Bahrul Maghfiroh Islamic Boarding School have an entrepreneurship program where students are given entrepreneurial knowledge and practice in business units at the Bahrul Maghfiroh Islamic Boarding School to foster interest in entrepreneurship among students. This research is quantitative research with path analysis technique or path analysis. The results showed a direct influence of entrepreneurial knowledge and self-efficacy on entrepreneurial motivation, and there was a direct influence of entrepreneurial knowledge and self-efficacy on entrepreneurial interest. There is a direct influence of entrepreneurial motivation on interest in entrepreneurship. Entrepreneurial knowledge has an indirect influence on interest in entrepreneurship through entrepreneurial motivation. Self-efficacy has an indirect influence on interest in entrepreneurship through entrepreneurial motivation